From Leaf to Topsoil, a Semi-quantitative Assessment of the Organic Matter Variations in Riparian Forests on a Lake Shore - Lila Siegfried; Renée-Claire Le Bayon; Eric Verrecchia; Pascal Vittoz (Wetlands, 2026)

Widespread Shrubification on European Mountain Summits - Thomas Vanneste; Harald Pauli; Stefan Dullinger; Bente J. Graae; Otar Abdaladze; José Luis Benito Alonso; Christopher Andrews; Peter Barančok; Manfred Bardy‐Durchhalter; Haben Blondeel; Pau Carnicero; Emmanuel Corcket; et al. (Global Change Biology, 2026)
Shrubs are expanding across the cold ecosystems of our planet with potentially profound consequences for their biodiversity and functioning. However, evidence is still strongly biased towards the Arctic tundra, while a large‐scale assessment of shrub expansion in alpine areas above the elevational treeline is missing so far. Here we quantified shrub cover changes over the past two decades in 576 permanent plots of 1 m 2 spread across the alpine vegetation belt of Europe's major mountain chains. Total shrub cover clearly increased in the plots with an average rate of about 2.6% per m 2 per decade (95% CI = 1.9%–3.4%), and this expansion was more pronounced for evergreen (2.0% per m 2 per decade, CI = 1.3%–2.7%) than for deciduous species (1.7% per m 2 per decade, CI = 0.9%–2.4%). The magnitude of individual species' cover shifts was positively associated with their plant height, but negatively with their leaf nitrogen content and light affinity. In sum, we show that shrub expansion is a widespread phenomenon also in the alpine zone of European mountains, with potentially far‐reaching consequences for alpine plant dynamics, soil microclimates, snow patterns, carbon cycling, food chains and livelihoods.

When Clearing Out an Old House Advances Science: The Hump‐Shaped Diversity Distribution in Central European Grasslands Better Explained - Pascal Vittoz (Global Change Biology, 2026)

Seed dispersal distance classes and dispersal modes for the European flora - Zdeňka Lososová; Irena Axmanová; Milan Chytrý; Gabriele Midolo; Sylvain Abdulhak; Dirk Nikolaus Karger; Julien Renaud; Jérémie Van Es; Pascal Vittoz; Wilfried Thuiller (Global Ecology and Biogeography, 2023)
Motivation Although dispersal ability is one of the key features determining the spatial dynamics of plant populations and the structure of plant communities, it is also one of the traits for which we still lack data for most species. We compiled a comprehensive dataset of seed dispersal distance classes and predominant dispersal modes for most European vascular plants. Our seed dispersal dataset can be used in functional biogeography, dynamic vegetation modelling and ecological studies at local to continental scales. Main Types of Variables Contained Species were classified into seven ordered classes with similar dispersal distances estimated based on the predominant dispersal mode, the morphology of dispersal units (diaspores or propagules), life form, plant height, seed mass, habitat and known dispersal by humans. We evaluated our results by comparing them with dispersal distances calculated using the ‘dispeRsal’ function in R. Spatial Location Europe. Time Period Present. Major Taxa and Level of Measurement The seed dispersal dataset contains information on dispersal distance classes and the predominant dispersal mode for 10,327 most frequent and locally dominant European vascular plant species. Software Format Data are available in .csv format.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Directional turnover towards larger‐ranged plants over time and across habitats - Ingmar R. Staude; Henrique M. Pereira; Gergana N. Daskalova; Markus Bernhardt‐Römermann; Martin Diekmann; Harald Pauli; Hans Van Calster; Mark Vellend; Anne D. Bjorkman; Jörg Brunet; Pieter De Frenne; Radim Hédl; et al. (Ecology Letters, 2022)
Species turnover is ubiquitous. However, it remains unknown whether certain types of species are consistently gained or lost across different habitats. Here, we analysed the trajectories of 1827 plant species over time intervals of up to 78 years at 141 sites across mountain summits, forests, and lowland grasslands in Europe. We found, albeit with relatively small effect sizes, displacements of smaller‐ by larger‐ranged species across habitats. Communities shifted in parallel towards more nutrient‐demanding species, with species from nutrient‐rich habitats having larger ranges. Because these species are typically strong competitors, declines of smaller‐ranged species could reflect not only abiotic drivers of global change, but also biotic pressure from increased competition. The ubiquitous component of turnover based on species range size we found here may partially reconcile findings of no net loss in local diversity with global species loss, and link community‐scale turnover to macroecological processes such as biotic homogenisation.

A common soil temperature threshold for the upper limit of alpine grasslands in European mountains - Sarah Bürli; Jean-Paul Theurillat; Manuela Winkler; Andrea Lamprecht; Harald Pauli; Christian Rixen; Klaus Steinbauer; Sonja Wipf; Otar Abdaladze; Christopher Andrews; Peter Barančok; José Luis Benito-Alonso; et al. (Alpine Botany, 2021)
While climatic research about treeline has a long history, the climatic conditions corresponding to the upper limit of closed alpine grasslands remain poorly understood. Here, we propose a climatic definition for this limit, the ‘grassline’, in analogy to the treeline, which is based on the growing season length and the soil temperature. Eighty-seven mountain summits across ten European mountain ranges, covering three biomes (boreal, temperate, Mediterranean), were inventoried as part of the GLORIA project. Vascular plant cover was estimated visually in 326 plots of 1 × 1 m. Soil temperatures were measured in situ for 2–7 years, from which the length of the growing season and mean temperature were derived. The climatic conditions corresponding to 40% plant cover were defined as the thresholds for alpine grassland. Closed vegetation was present in locations with a mean growing season soil temperature warmer than 4.9 °C, or a minimal growing season length of 85 days, with the growing season defined as encompassing days with daily mean ≥ 1 °C. Hence, the upper limit of closed grasslands was associated with a mean soil temperature close to that previously observed at the treeline, and in accordance with physiological thresholds to growth in vascular plants. In contrast to trees, whose canopy temperature is coupled with air temperature, small-stature alpine plants benefit from the soil warmed by solar radiation and consequently, they can grow at higher elevations. Since substrate stability is necessary for grasslands to occur at their climatic limit, the grassline rarely appears as a distinct linear feature.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Contrasting impacts of climate change on the vegetation of windy ridges and snowbeds in the Swiss Alps - Loïc Liberati; Swanee Messerli; Magalì Matteodo; Pascal Vittoz (Alpine Botany, 2019)

Learning from model errors: Can land use, edaphic and very high‐resolution topo‐climatic factors improve macroecological models of mountain grasslands? - Maude E. A. Baudraz; Jean‐Nicolas Pradervand; Mélanie Beauverd; Aline Buri; Antoine Guisan; Pascal Vittoz (Journal of Biogeography, 2018)
Aim Assess the potential of new predictors (land use, edaphic factors and high‐resolution (HR) topographic and climatic variables, i.e. topo‐climatic) to improve the prediction of plant community functional traits (specific leaf area, vegetative height and seed mass) and species richness in models of mountain grasslands. Location The western Swiss Alps. Methods Using 912 grassland plots, we constructed predictive models for community‐weighted means of plant traits and species richness using HR (25 m) topo‐climatic predictors traditionally used in previous modelling studies in this area. In addition, 78 new plots were sampled for evaluation and error assessment in four narrower sets of homogenous conditions based on predictions by the topo‐climatic models within two elevational belts (montane and alpine). New, finer‐scale predictors were generated from direct field measurements or very high‐resolution (VHR; 5 m) numerical data. We then used multimodel inference to test the capacity of these finer predictors to explain part of the residual variance in the initial topo‐climatic models. Results We showed that the finer‐scale predictors explained up to 44% of the residual variance in the classical topo‐climatic models. The VHR topographic position, soil C/N ratio and pH performed notably well in our analysis. Land use (farming intensity) was highlighted as potentially important in montane grasslands, but improvements were only significant for species richness predictions. Main conclusions Compared with previously used topo‐climatic models, the new, finer‐scale predictors significantly improved the prediction of all traits and species richness in alpine plant communities and that of specific leaf area and richness in montane grasslands. The differences in the importance of the predictors, dependent on both trait and position along the elevational gradient, highlight the different factors that shape the distribution of species and communities along elevational gradients.

Uneven rate of plant turnover along elevation in grasslands - Patrice Descombes; Pascal Vittoz; Antoine Guisan; Loïc Pellissier (Alpine Botany, 2017)

Community-level relaxation of plant defenses against herbivores at high elevation - Kristine Callis-Duehl; Pascal Vittoz; Emmanuel Defossez; Sergio Rasmann (Plant Ecology, 2017)

Monitoring and distribution modelling of invasive species along riverine habitats at very high resolution - Patrice Descombes; Blaise Petitpierre; Eric Morard; Michael Berthoud; Antoine Guisan; Pascal Vittoz (Biological Invasions, 2016)

The rich sides of mountain summits – a pan‐European view on aspect preferences of alpine plants - Manuela Winkler; Andrea Lamprecht; Klaus Steinbauer; Karl Hülber; Jean‐Paul Theurillat; Frank Breiner; Philippe Choler; Siegrun Ertl; Alba Gutiérrez Girón; Graziano Rossi; Pascal Vittoz; Maia Akhalkatsi; et al. (Journal of Biogeography, 2016)
Aim In the alpine life zone, plant diversity is strongly determined by local topography and microclimate. We assessed the extent to which aspect and its relatedness to temperature affect plant species diversity, and the colonization and disappearance of species on alpine summits on a pan‐European scale. Location Mountain summits in Europe's alpine life zone. Methods Vascular plant species and their percentage cover were recorded in permanent plots in each cardinal direction on 123 summits in 32 regions across Europe. For a subset from 17 regions, resurvey data and 6‐year soil temperature series were available. Differences in temperature sum and Shannon index as well as species richness, colonization and disappearance of species among cardinal directions were analysed using linear mixed‐effects and generalised mixed‐effects models, respectively. Results Temperature sums were higher in east‐ and south‐facing aspects than in the north‐facing ones, while the west‐facing ones were intermediate; differences were smallest in northern Europe. The patterns of temperature sums among aspects were consistent among years. In temperate regions, thermal differences were reflected by plant diversity, whereas this relationship was weaker or absent on Mediterranean and boreal mountains. Colonization of species was positively related to temperature on Mediterranean and temperate mountains, whereas disappearance of species was not related to temperature. Main conclusions Thermal differences caused by solar radiation determine plant species diversity on temperate mountains. Advantages for plants on eastern slopes may result from the combined effects of a longer diurnal period of radiation due to convection cloud effects in the afternoon and the sheltered position against the prevailing westerly winds. In northern Europe, long summer days and low sun angles can even out differences among aspects. On Mediterranean summits, summer drought may limit species numbers on the warmer slopes. Warmer aspects support a higher number of colonization events. Hence, aspect can be a principal determinant of the pace of climate‐induced migration processes.

A matter of scale: apparent niche differentiation of diploid and tetraploid plants may depend on extent and grain of analysis - Bernhard Kirchheimer; Christoph C. F. Schinkel; Agnes S. Dellinger; Simone Klatt; Dietmar Moser; Manuela Winkler; Jonathan Lenoir; Marco Caccianiga; Antoine Guisan; Diego Nieto‐Lugilde; Jens‐Christian Svenning; Wilfried Thuiller; et al. (Journal of Biogeography, 2016)
Aim Emerging polyploids may depend on environmental niche shifts for successful establishment. Using the alpine plant Ranunculus kuepferi as a model system, we explore the niche shift hypothesis at different spatial resolutions and in contrasting parts of the species range. Location European Alps. Methods We sampled 12 individuals from each of 102 populations of R. kuepferi across the Alps, determined their ploidy levels, derived coarse‐grain (100 × 100 m) environmental descriptors for all sampling sites by downscaling WorldClim maps, and calculated fine‐scale environmental descriptors (2 × 2 m) from indicator values of the vegetation accompanying the sampled individuals. Both coarse and fine‐scale variables were further computed for 8239 vegetation plots from across the Alps. Subsequently, we compared niche optima and breadths of diploid and tetraploid cytotypes by combining principal components analysis and kernel smoothing procedures. Comparisons were done separately for coarse and fine‐grain data sets and for sympatric, allopatric and the total set of populations. Results All comparisons indicate that the niches of the two cytotypes differ in optima and/or breadths, but results vary in important details. The whole‐range analysis suggests differentiation along the temperature gradient to be most important. However, sympatric comparisons indicate that this climatic shift was not a direct response to competition with diploid ancestors. Moreover, fine‐grained analyses demonstrate niche contraction of tetraploids, especially in the sympatric range, that goes undetected with coarse‐grained data. Main conclusions Although the niche optima of the two cytotypes differ, separation along ecological gradients was probably less decisive for polyploid establishment than a shift towards facultative apomixis, a particularly effective strategy to avoid minority cytotype exclusion. In addition, our results suggest that coarse‐grained analyses overestimate niche breadths of widely distributed taxa. Niche comparison analyses should hence be conducted at environmental data resolutions appropriate for the organism and question under study.

Past climate‐driven range shifts and population genetic diversity in arctic plants - Loïc Pellissier; Pernille Bronken Eidesen; Dorothee Ehrich; Patrice Descombes; Peter Schönswetter; Andreas Tribsch; Kristine Bakke Westergaard; Nadir Alvarez; Antoine Guisan; Niklaus E. Zimmermann; Signe Normand; Pascal Vittoz; et al. (Journal of Biogeography, 2016)
Aim High intra‐specific genetic diversity is necessary for species adaptation to novel environments under climate change, but species tracking suitable conditions are losing alleles through successive founder events during range shift. Here, we investigated the relationship between range shift since the Last Glacial Maximum ( LGM ) and extant population genetic diversity across multiple plant species to understand variability in species responses. Location The circumpolar Arctic and northern temperate alpine ranges. Methods We estimated the climatic niches of 30 cold‐adapted plant species using range maps coupled with species distribution models and hindcasted species suitable areas to reconstructions of the mid‐Holocene and LGM climates. We computed the species‐specific migration distances from the species glacial refugia to their current distribution and correlated distances to extant genetic diversity in 1295 populations. Differential responses among species were related to life‐history traits. Results We found a negative association between inferred migration distances from refugia and genetic diversities in 25 species, but only 11 had statistically significant negative slopes. The relationships between inferred distance and population genetic diversity were steeper for insect‐pollinated species than wind‐pollinated species, but the difference among pollination system was marginally independent from phylogenetic autocorrelation. Main conclusion The relationships between inferred migration distances and genetic diversities in 11 species, independent from current isolation, indicate that past range shifts were associated with a genetic bottleneck effect with an average of 21% loss of genetic diversity per 1000 km −1 . In contrast, the absence of relationship in many species also indicates that the response is species specific and may be modulated by plant pollination strategies or result from more complex historical contingencies than those modelled here.

Disjunct populations of E uropean vascular plant species keep the same climatic niches - Safaa Wasof; Jonathan Lenoir; Per Arild Aarrestad; Inger Greve Alsos; W. Scott Armbruster; Gunnar Austrheim; Vegar Bakkestuen; H. John B. Birks; Kari Anne Bråthen; Olivier Broennimann; Jörg Brunet; Hans Henrik Bruun; et al. (Global Ecology and Biogeography, 2015)
Aim Previous research on how climatic niches vary across species ranges has focused on a limited number of species, mostly invasive, and has not, to date, been very conclusive. Here we assess the degree of niche conservatism between distant populations of native alpine plant species that have been separated for thousands of years. Location European A lps and F ennoscandia. Methods Of the studied pool of 888 terrestrial vascular plant species occurring in both the A lps and F ennoscandia, we used two complementary approaches to test and quantify climatic‐niche shifts for 31 species having strictly disjunct populations and 358 species having either a contiguous or a patchy distribution with distant populations. First, we used species distribution modelling to test for a region effect on each species' climatic niche. Second, we quantified niche overlap and shifts in niche width (i.e. ecological amplitude) and position (i.e. ecological optimum) within a bi‐dimensional climatic space. Results Only one species (3%) of the 31 species with strictly disjunct populations and 58 species (16%) of the 358 species with distant populations showed a region effect on their climatic niche. Niche overlap was higher for species with strictly disjunct populations than for species with distant populations and highest for arctic–alpine species. Climatic niches were, on average, wider and located towards warmer and wetter conditions in the Alps. Main conclusion Climatic niches seem to be generally conserved between populations that are separated between the A lps and F ennoscandia and have probably been so for 10,000–15,000 years. Therefore, the basic assumption of species distribution models that a species' climatic niche is constant in space and time – at least on time scales 10 4 years or less – seems to be largely valid for arctic–alpine plants.

Clonal growth and demography of a hemicryptophyte alpine plant: Leontopodium alpinum Cassini - Roland Keller; Pascal Vittoz (Alpine Botany, 2015)

Scale decisions can reverse conclusions on community assembly processes - Tamara Münkemüller; Laure Gallien; Sébastien Lavergne; Julien Renaud; Cristina Roquet; Sylvain Abdulhak; Stefan Dullinger; Luc Garraud; Antoine Guisan; Jonathan Lenoir; Jens‐Christian Svenning; Jérémie Van Es; et al. (Global Ecology and Biogeography, 2014)
Aim Phylogenetic diversity patterns are increasingly being used to better understand the role of ecological and evolutionary processes in community assembly. Here, we quantify how these patterns are influenced by scale choices in terms of spatial and environmental extent and organismic scales. Location E uropean A lps. Methods We applied 42 sampling strategies differing in their combination of focal scales. For each resulting sub‐dataset, we estimated the phylogenetic diversity of the species pools, phylogenetic α‐diversities of local communities, and statistics commonly used together with null models in order to infer non‐random diversity patterns (i.e. phylogenetic clustering versus over‐dispersion). Finally, we studied the effects of scale choices on these measures using regression analyses. Results Scale choices were decisive for revealing signals in diversity patterns. Notably, changes in focal scales sometimes reversed a pattern of over‐dispersion into clustering. Organismic scale had a stronger effect than spatial and environmental extent. However, we did not find general rules for the direction of change from over‐dispersion to clustering with changing scales. Importantly, these scale issues had only a weak influence when focusing on regional diversity patterns that change along abiotic gradients. Main conclusions Our results call for caution when combining phylogenetic data with distributional data to study how and why communities differ from random expectations of phylogenetic relatedness. These analyses seem to be robust when the focus is on relating community diversity patterns to variation in habitat conditions, such as abiotic gradients. However, if the focus is on identifying relevant assembly rules for local communities, the uncertainty arising from a certain scale choice can be immense. In the latter case, it becomes necessary to test whether emerging patterns are robust to alternative scale choices.

Thermal niches are more conserved at cold than warm limits in arctic‐alpine plant species - Loïc Pellissier; Kari Anne Bråthen; Pascal Vittoz; Nigel G. Yoccoz; Anne Dubuis; Eliane S. Meier; Niklaus E. Zimmermann; Christophe F. Randin; Wilfried Thuiller; Luc Garraud; Jérémie Van Es; Antoine Guisan (Global Ecology and Biogeography, 2013)
Aim Understanding the stability of realized niches is crucial for predicting the responses of species to climate change. One approach is to evaluate the niche differences of populations of the same species that occupy regions that are geographically disconnected. Here, we assess niche conservatism along thermal gradients for 26 plant species with a disjunct distribution between the A lps and the A rctic. Location E uropean A lps and N orwegian F innmark. Methods We collected a comprehensive dataset of 26 arctic‐alpine plant occurrences in two regions. We assessed niche conservatism through a multispecies comparison and analysed species rankings at cold and warm thermal limits along two distinct gradients corresponding to (1) air temperatures at 2 m above ground level and (2) elevation distances to the tree line ( TLD ) for the two regions. We assessed whether observed relationships were close to those predicted under thermal limit conservatism. Results We found a weak similarity in species ranking at the warm thermal limits. The range of warm thermal limits for the 26 species was much larger in the Alps than in Finnmark. We found a stronger similarity in species ranking and correspondence at the cold thermal limit along the gradients of 2‐m temperature and TLD . Yet along the 2‐m temperature gradient the cold thermal limits of species in the Alps were lower on average than those in Finnmark. Main conclusion We found low conservatism of the warm thermal limits but a stronger conservatism of the cold thermal limits. We suggest that biotic interactions at the warm thermal limit are likely to modulate species responses more strongly than at the cold limit. The differing biotic context between the two regions is probably responsible for the observed differences in realized niches.

The accuracy of plant assemblage prediction from species distribution models varies along environmental gradients - Julien Pottier; Anne Dubuis; Loïc Pellissier; Luigi Maiorano; Leila Rossier; Christophe F. Randin; Pascal Vittoz; Antoine Guisan (Global Ecology and Biogeography, 2013)
Aim Climatic niche modelling of species and community distributions implicitly assumes strong and constant climatic determinism across geographical space. We tested this assumption by assessing how stacked‐species distribution models ( S ‐ SDMs ) perform for predicting plant species assemblages along elevation gradients. Location The western S wiss A lps. Methods Using robust presence–absence data, we first assessed the ability of topo‐climatic S ‐ SDMs to predict plant assemblages in a study area encompassing a 2800‐m wide elevation gradient. We then assessed the relationships among several evaluation metrics and trait‐based tests of community assembly rules. Results The standard errors of individual SDMs decreased significantly towards higher elevations. Overall, the S ‐ SDM overpredicted far more than they underpredicted richness and could not reproduce the humpback curve along elevation. Overprediction was greater at low and mid‐range elevations in absolute values but greater at high elevations when standardized by the actual richness. Looking at species composition, overall prediction success, kappa and specificity increased with increasing elevation, while the Jaccard index and sensitivity decreased. The best overall evaluation – as driven by specificity – occurred at high elevation where species assemblages were shown to be subject to significant environmental filtering of small plants. In contrast, the decreased overall accuracy in the lowlands was associated with functional patterns representing any type of assembly rule (environmental filtering, limiting similarity or null assembly). Main conclusions We provide a thorough evaluation of S ‐ SDM emphasizing the need to carefully interpret standard evaluation metrics, which reflect different aspects of assemblage predictions. We further reported interesting patterns of change in S ‐ SDM errors with changes in assembly rules along elevation. Yet, significant levels of assemblage prediction errors occurred throughout the gradient, calling for further improvement of SDMs , e.g. by adding key environmental filters that act at fine scales and developing approaches to account for variations in the influence of predictors along environmental gradients.

Improving plant functional groups for dynamic models of biodiversity: at the crossroads between functional and community ecology - Isabelle Boulangeat; Pauline Philippe; Sylvain Abdulhak; Roland Douzet; Luc Garraud; Sébastien Lavergne; Sandra Lavorel; Jérémie Van Es; Pascal Vittoz; Wilfried Thuiller (Global Change Biology, 2012)
The pace of on‐going climate change calls for reliable plant biodiversity scenarios. Traditional dynamic vegetation models use plant functional types that are summarized to such an extent that they become meaningless for biodiversity scenarios. Hybrid dynamic vegetation models of intermediate complexity (hybrid‐ DVM s) have recently been developed to address this issue. These models, at the crossroads between phenomenological and process‐based models, are able to involve an intermediate number of well‐chosen plant functional groups ( PFG s). The challenge is to build meaningful PFG s that are representative of plant biodiversity, and consistent with the parameters and processes of hybrid‐ DVM s. Here, we propose and test a framework based on few selected traits to define a limited number of PFG s, which are both representative of the diversity (functional and taxonomic) of the flora in the E crins N ational P ark, and adapted to hybrid‐ DVM s. This new classification scheme, together with recent advances in vegetation modeling, constitutes a step forward for mechanistic biodiversity modeling.

Plant traits co-vary with altitude in grasslands and forests in the European Alps - Loïc Pellissier; Bertrand Fournier; Antoine Guisan; Pascal Vittoz (Plant Ecology, 2010)

Importance of abiotic stress as a range‐limit determinant for European plants: insights from species responses to climatic gradients - Signe Normand; Urs A. Treier; Christophe Randin; Pascal Vittoz; Antoine Guisan; Jens‐Christian Svenning (Global Ecology and Biogeography, 2009)
Aim We examined whether species occurrences are primarily limited by physiological tolerance in the abiotically more stressful end of climatic gradients (the asymmetric abiotic stress limitation (AASL) hypothesis) and the geographical predictions of this hypothesis: abiotic stress mainly determines upper‐latitudinal and upper‐altitudinal species range limits, and the importance of abiotic stress for these range limits increases the further northwards and upwards a species occurs. Location Europe and the Swiss Alps. Methods The AASL hypothesis predicts that species have skewed responses to climatic gradients, with a steep decline towards the more stressful conditions. Based on presence–absence data we examined the shape of plant species responses (measured as probability of occurrence) along three climatic gradients across latitudes in Europe (1577 species) and altitudes in the Swiss Alps (284 species) using Huisman–Olff–Fresco, generalized linear and generalized additive models. Results We found that almost half of the species from Europe and one‐third from the Swiss Alps showed responses consistent with the predictions of the AASL hypothesis. Cold temperatures and a short growing season seemed to determine the upper‐latitudinal and upper‐altitudinal range limits of up to one‐third of the species, while drought provided an important constraint at lower‐latitudinal range limits for up to one‐fifth of the species. We found a biome‐dependent influence of abiotic stress and no clear support for abiotic stress as a stronger upper range‐limit determinant for species with higher latitudinal and altitudinal distributions. However, the overall influence of climate as a range‐limit determinant increased with latitude. Main conclusions Our results support the AASL hypothesis for almost half of the studied species, and suggest that temperature‐related stress controls the upper‐latitudinal and upper‐altitudinal range limits of a large proportion of these species, while other factors including drought stress may be important at the lower range limits.

Climate change and plant distribution: local models predict high‐elevation persistence - CHRISTOPHE F. RANDIN; ROBIN ENGLER; SIGNE NORMAND; MASSIMILIANO ZAPPA; NIKLAUS E. ZIMMERMANN; PETER B. PEARMAN; PASCAL VITTOZ; WILFRIED THUILLER; ANTOINE GUISAN (Global Change Biology, 2009)
Mountain ecosystems will likely be affected by global warming during the 21st century, with substantial biodiversity loss predicted by species distribution models (SDMs). Depending on the geographic extent, elevation range, and spatial resolution of data used in making these models, different rates of habitat loss have been predicted, with associated risk of species extinction. Few coordinated across‐scale comparisons have been made using data of different resolutions and geographic extents. Here, we assess whether climate change‐induced habitat losses predicted at the European scale (10 × 10′ grid cells) are also predicted from local‐scale data and modeling (25 m × 25 m grid cells) in two regions of the Swiss Alps. We show that local‐scale models predict persistence of suitable habitats in up to 100% of species that were predicted by a European‐scale model to lose all their suitable habitats in the area. Proportion of habitat loss depends on climate change scenario and study area. We find good agreement between the mismatch in predictions between scales and the fine‐grain elevation range within 10 × 10′ cells. The greatest prediction discrepancy for alpine species occurs in the area with the largest nival zone. Our results suggest elevation range as the main driver for the observed prediction discrepancies. Local‐scale projections may better reflect the possibility for species to track their climatic requirement toward higher elevations.

Low impact of climate change on subalpine grasslands in the Swiss Northern Alps - PASCAL VITTOZ; CHRISTOPHE RANDIN; ANNELISE DUTOIT; FRANÇOIS BONNET; OTTO HEGG (Global Change Biology, 2009)
While phenological shifts and migration of isolated species under climate change have already been observed on alpine summits, very few studies have focused on community composition changes in subalpine grasslands. Here we use permanent plots monitored since 1954 and precisely located phytosociological censuses from 1970 to study compositional changes of subalpine grasslands in two distinct regions of the Swiss Northern Alps. In both areas, warming trends during the monitoring period were associated with changes in land management (abandonment of goat and sheep pasturing or grazing replaced by mowing). Old and recent inventories were compared with correspondence analyses (CA). Ecological indicator values, community‐affinities and biological traits of the species were used to infer the factors responsible for triggering the observed changes. In both regions, subalpine grasslands were stable with smaller changes than have previously been observed in alpine environments. Only a few species appeared or disappeared and changes were generally limited to increasing or decreasing frequency and cover of certain taxa. At one site, grazing abandonment favored fallow species. Some of these species were located at their upper altitudinal distribution limits and may have spread because of rising temperatures. In both areas, declining species were predominantly alpine and low‐growing species; their decline was probably due to increased competition (e.g., shadow) with more vigorous subalpine taxa no longer limited by grazing. We conclude that vegetation communities can respond rapidly to warming as long as colonization is facilitated by available space or structural change. In the subalpine grasslands studies, changes were mainly driven by land management. These communities have a dense vegetation cover and newly arriving herbaceous species preferring warmer conditions may take some time to establish themselves. However, climate disturbances, such as exceptional drought, may accelerate community changes by opening gaps for new species.

Pollen productivity estimates and relevant source area of pollen for selected plant taxa in a pasture woodland landscape of the Jura Mountains (Switzerland) - Florence Mazier; Anna Broström; Marie-José Gaillard; Shinya Sugita; Pascal Vittoz; Alexandre Buttler (Vegetation History and Archaeobotany, 2008)

Prediction of plant species distributions across six millennia - Peter B. Pearman; Christophe F. Randin; Olivier Broennimann; Pascal Vittoz; Willem O. van der Knaap; Robin Engler; Gwenaelle Le Lay; Niklaus E. Zimmermann; Antoine Guisan (Ecology Letters, 2008)
The usefulness of species distribution models (SDMs) in predicting impacts of climate change on biodiversity is difficult to assess because changes in species ranges may take decades or centuries to occur. One alternative way to evaluate the predictive ability of SDMs across time is to compare their predictions with data on past species distributions. We use data on plant distributions, fossil pollen and current and mid‐Holocene climate to test the ability of SDMs to predict past climate‐change impacts. We find that species showing little change in the estimated position of their realized niche, with resulting good model performance, tend to be dominant competitors for light. Different mechanisms appear to be responsible for among‐species differences in model performance. Confidence in predictions of the impacts of climate change could be improved by selecting species with characteristics that suggest little change is expected in the relationships between species occurrence and climate patterns.